Preventing Mass Human-Rights Violations and Atrocity Crimes - Bieńczyk-Missala, Angieszka (Studies in Politics, Security and Society, 2021)
The problem of preventing mass human-rights violations and atrocity crimes is one of the key issues in international relations. The book presents the capacity of the international community in the field. The available instruments of early warning, preventive diplomacy as well as legal, economic, and military measures of prevention are included. Cases of Chechnya, Rwanda, Côte d'Ivoire and Libya allowed the analysis of international engagement in typical situations involving mass human-rights violations and atrocity crimes related to self-determination, ethnic tensions, power struggles and attempts to overthrow a dictatorship. They show that although the international community has significantly increased its capacity to prevent, it has not created a coherent system of prevention.